2019
DOI: 10.1016/j.ijcard.2018.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Peri-procedural brain lesions prevention in CAS (3PCAS): Randomized trial comparing CGuard™ stent vs. Wallstent™

Abstract: Background: Aim of this study was to evaluate peri-procedural incidence of new diffusion-weighted-magneticresonance-imaging (DWMRI) brain lesions in CAS patients treated by carotid mesh stent (CGuard™) or closed-cell stent (Wallstent™). Methods: Consecutive patients with asymptomatic carotid stenosis ≥ 70% were submitted to preoperative DW-MRI scan, to exclude the presence of preoperative silent cerebral lesions. Patients were randomized to CGuard or Wallstent. DWMRI was performed immediately after the interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…However, recent studies with CGUARD reported that new ipsilateral ischemic lesions occurred in 31%% to 37% of cases. 9,24 Our results seemed be similar or superior to those reported in the CGUARD studies, although baseline characteristics of the patients were different. The closed-cell stent-in-stent technique might be an alternative to micromesh stents.…”
Section: Discussionsupporting
confidence: 84%
“…However, recent studies with CGUARD reported that new ipsilateral ischemic lesions occurred in 31%% to 37% of cases. 9,24 Our results seemed be similar or superior to those reported in the CGUARD studies, although baseline characteristics of the patients were different. The closed-cell stent-in-stent technique might be an alternative to micromesh stents.…”
Section: Discussionsupporting
confidence: 84%
“…Despite some benefits expected from the use of closedcell stents, dueto their low flexibility, the delivery of closedcell stents may be difficult in tortuous vessels. 29 To address this important limitation, new carotid stents, known as duallayered mesh-covered carotid stent systems, were introduced. This technology combines optimal flexibility (open-cell stents feature) with improved embolic prevention (closed-cell stents feature).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the micromesh of the Roadsaver/Casper and Cguard stents was designed to allow trapping debris between the stent scaffold and the vessel wall. 15,29,30 Plaque prolapse, as assessed by optical coherence tomography (OCT), was demonstrated to be a rare event whenusing micromesh stents. 15,24,31,32 Nerla et al 15 demonstrated that plaque material did not go beyond the second row of struts of the double mesh stent in all patients assessed with OCT, being entrapped between the 2 layers of struts.…”
Section: Discussionmentioning
confidence: 99%
“…59 It is important to note that the outcome difference between the conventional-stent CAS vs CEA and between the conventional-stent CAS vs a dual-layer stent CAS likewise is driven by high-risk patients and plaques. 16,[33][34][35][36][37] Therefore, to provide clinically-relevant answers, carotid revascularization studies should strive to include highrisk 58,59 rather than low-risk 60 patients. As evidenced in cardiovascular studies in other areas, inclusion of low(er)-risk patients and low(er)-risk lesions (while assigning their high(er)-risk counterparts to intervention outside the study) leads to generating "answers" that are not relevant to clinical practice involving significant proportions of high-risk patients.…”
mentioning
confidence: 99%
“…As evidenced in cardiovascular studies in other areas, inclusion of low(er)-risk patients and low(er)-risk lesions (while assigning their high(er)-risk counterparts to intervention outside the study) leads to generating “answers” that are not relevant to clinical practice involving significant proportions of high-risk patients. 60 An example is a recent randomized study of coronary thrombus aspiration in acute myocardial infarction where one fundamental reason not to enroll in the study was the operator’s conviction that the patient required the study-tested intervention. 61 While this is certainly right ethically, such studies are no longer able to provide answers relevant to real-life patient management.…”
mentioning
confidence: 99%